Exploring member perspectives on participation on child welfare Citizen Review Panels: A national study. (October 2017) - Miller, J. Jay; Collins-Camargo, Crystal; Jones, Blake; Niu, Chunling
Abstract: The year 2016 marked the 20th anniversary of the Child Abuse Prevention and Treatment Act (CAPTA) amendments (P.L. 104–235) that mandated Citizen Review Panels (CRPs). CRPs are citizen volunteer groups authorized by United States (U.S.) federal law to examine policies and procedures of state child welfare agencies. Despite the potential of CRPs to positively impact child welfare systems outcomes associated with child abuse and neglect, and the millions of dollars in resources allocated to these groups, there remains a dearth in the literature about CRPs. This exploratory study examined CRP member perceptions from across the United States. Researchers collected scaled survey data to examine member knowledge, engagement and assessment of panel influence and impact, membership composition, and meeting structure. Results revealed that panel members lack some knowledge related to the federal mandate guiding their work, and data suggest the need for panels to more adroitly recruit and retain members representative of the communities in which the panels are formed. After a brief review of background literature, this paper will explicate key results, discuss these findings, and identify salient practice, policy and research implications derived from the study.